Kalender Islam Global Antara Dilema dan Darurat - Nur Anshari Anshari (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2017)
AbstractThe preparation of the Global Islamic calendar along with the congress has been held in Turkey several months ago and resulted in a deal to be the Global Islamic calendar manifold single global calendar. In this paper the authors try to explore the opinions of experts related to the determination of the Islamic calendar. Is single calendar globally agreed upon at the congress Turkey was able to answer the question ijtihadiah far. Then how hilal criteria used in preparing the global Islamic calendar later. Thus, the author tries to explore astronomy expert opinion in defining the new moon, the proper method to pay attention and make sure that there is or not the new moon, or of the new moon is visible or not. It needs a long discourse and party to contribute in the preparation of a global Islamic calendar. After performing a search that rentet and complicated, can be given a red thread on criteria suitable for structured calendar is based on the visibility of the new moon. Not only looking at the height of the new moon or the elongation angle per se, but more than that. With visibility of the new moon map we were able to predict which areas are able to observe the new moon and which are not.Keyword: calendar, visibility, newmoon